MANHAJ TAFSIR AL-QUR’AN AL-AZHIM KARYA IBNU KATSIR DALAM MENAFSIRKAN SURAT AL-MA’UN - Ihsan Imaduddin; Eni Zulaiha (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
The purpose of this study was to find out the characteristic of al-Quran commentary from Ahmad Musthafa al-Maraghi. The method used in this research is qualitative method or library research. The results of the research found that based on fifty years experience as an Arabic teacher, al-Maraghi’s commentary was written in simple expression that easily to be understood. His book of commentary published for the first time in 1951. The commentary of Al-Maraghi was using analytical or tahlili method. The explanation originates from the primary source in the form of the Qur'an, Hadith, Qaul Companions, Qaul tabi'in, as well as the opinions of other scholars as secondary source. The systematics adopted by Al-Maraghi is to mention the name of the sura and the number of verses, mention madaniyah or makkiyah, general explanation of each sura, asbab nuzul, explanation of selected vocabulary, using simple expression, detail explanation of each verse, and strictly selective to israiliyat story